Few‐Layered ReS2@CNTs as a High‐Performance Cathode for Aluminum‐Ion Batteries. Issue 18 (26th May 2022) - Gao, Kun; Lin, Xiangyun; Yu, Wenjing; Cheng, Xiurui; Zhang, Shaohua; Li, Shuning; Zhang, Zhipan
Abstract: With a high theoretical specific capacity of 2978 mAh g −1, rechargeable aluminum‐ion batteries (AIBs) are considered as promising next‐generation energy storage devices with higher electrochemical performance. Nevertheless, the search for stable cathode materials with outstanding capacity and rate performance remains elusive. In current work, few‐layered ReS2 is in situ grown on carbon nanotubes (CNTs) to form the ReS2 @CNTs composite. As ReS2 features a large interlayer spacing of ≈0.65 nm, the extremely weak interlayer coupling can effectively reduce the electrostatic repulsion between Al 3+ ions and the cathode host, adequately accommodating large amounts of Al 3+ ions without significant volume expansion. When it serves as the cathode in the AIB, ReS2 @CNTs delivers a high discharge specific capacity of 396.3 mA h g −1 and Coulombic efficiencies of ≈100% both after 250 cycles at a low rate (200 mA g −1 ) and 10 000 cycles under a higher rate (1 A g −1 ). Theoretical simulations and ex situ grazing incidence angle X‐ray diffraction results reveal that Al 3+ cations can be favorably and reversibly intercalated/deintercalated into the ReS2 @CNTs during the discharge/charge process. This work provides new insights into AIB chemistry and paves the way for the development of high‐performance AIBs. Abstract : A novel material, ReS2 @CNTs, is in situ hydrothermal synthesized at a low temperature of 160 °C and applied in high‐performance secondary aluminum‐ion battery cathodes (discharge specific capacity: 396.3 mA h g −1 ; Coulombic efficiencies: ≈100%). The working mechanism is proved as reversible intercalation/deintercalation of Al 3+ ions between ReS2 layers by experimental and theoretical results.